KESESUAIAN EKOWISATA SNORKLING DI PERAIRAN PULAU PANJANG JEPARA JAWA TENGAH - Indarjo, Agus (Jurnal Harpodon Borneo, 2015)
This research purposed at determining the suitability of the waters of Panjang Island for snorkling ecotourism activities. Biogeophysical data were collected by field survey. Method of data analysis comprises analysis of land and waters suitability and spatial analysis using GIS. Analysis results of the waters Panjang Island suitability for snorkling ecotourism activities categories class suitable at station 2, station 3, station 4, station 5 and station 6.Key words : Snorkeling ecotourism, waters suitable, Panjang island